2011
DOI: 10.1002/pat.1592
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NCO/OH ratio and Ce‐Zr nanoparticles on the thermo‐mechanical properties of hyperbranched polyurethane urea coatings

Abstract: The present study describes the effect of NCO/OH ratio and addition of Cerium (Ce)‐Zirconium (Zr) mixed oxide nanoparticles on the properties of Hyperbranched Polyurethane Urea (HBPUU) Coatings. Initially a hydroxyl terminated hyperbranched polymer (HTBP) was synthesized through A3 + CB2 approach. The HTBP and Ce‐Zr nanopowder dispersed HTBP, both were reacted with hexamethylene diisocyanate (HDI) separately; at various NCO/OH eq. ratios to get different NCO terminated HBPU and HBPU/Ce‐Zr hybrid prepolymers. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…The conclusion can be proved by the fact that the value of ΔW 1 % coincides with the value of hard% (shown in Table 6). In addition, the data of T 1on and Tgs coincide with the content of hydrogen bonding (shown in Figure 7), due to the fact that the more the hydrogen bonding, the more is the crosslink density, which brings the polymer backbones closer and thus reduces the molecular mobility, and increases the thermal stability and Tg [28,38]. The second and third decomposition data, shown in Table 6, have no obvious rules.…”
Section: Sample Name T 1on (°C) T 1max (°C) T 1end (°C) δW 1 a (%) Hamentioning
confidence: 66%
See 3 more Smart Citations
“…The conclusion can be proved by the fact that the value of ΔW 1 % coincides with the value of hard% (shown in Table 6). In addition, the data of T 1on and Tgs coincide with the content of hydrogen bonding (shown in Figure 7), due to the fact that the more the hydrogen bonding, the more is the crosslink density, which brings the polymer backbones closer and thus reduces the molecular mobility, and increases the thermal stability and Tg [28,38]. The second and third decomposition data, shown in Table 6, have no obvious rules.…”
Section: Sample Name T 1on (°C) T 1max (°C) T 1end (°C) δW 1 a (%) Hamentioning
confidence: 66%
“…It is reported that the dendritic units different chemical shifts of 13 C NMR [28]. The marks of dendritic units (D), linear units (L) and terminal units (T) are shown in Figure 2A and W T &W L &W D represent the -N-CH 2 -zone (W) which stays in different units.…”
Section: Nmr Analysismentioning
confidence: 97%
See 2 more Smart Citations
“…The PU is well-known for their outstanding abrasion resistance, corrosion resistance, excellent flexibility, strong adhesion to substrates, possibility of tailoring properties, and also some other specific properties [3][4][5][6] . Therefore, it is widely used in manufacture industry, daily life, health care, and even the national defense industry.…”
Section: Introductionmentioning
confidence: 99%